Host CD39 Deficiency Affects Radiation-Induced Tumor Growth Delay and Aggravates Radiation-Induced Normal Tissue Toxicity - Meyer, Alina V.; Klein, Diana; de Leve, Simone; Szymonowicz, Klaudia; Stuschke, Martin; Robson, Simon C.; Jendrossek, Verena; Wirsdörfer, Florian (Frontiers in Oncology, 2020)
The ectonucleoside triphosphate diphosphohydrolase (CD39)/5´ectonuclotidase (CD73)-dependent purinergic pathway emerges as promising cancer target. Yet except for own previous work revealing a pathogenic role of CD73 and adenosine in radiation-induced lung fibrosis, the role of purinergic signaling for radiotherapy outcome remained elusive. Here we used C57BL/6 wildtype (WT), CD39 knockout (CD39-/-), and CD73 knockout (CD73-/-) mice and hind-leg tumors of syngeneic murine Lewis lung carcinoma cells (LLC1) to elucidate how host purinergic signaling shapes the growth of LLC1 tumors to a single high dose irradiation with 10 Gy in vivo. In complementary in vitro experiments we examined the radiation response of LLC1 cells in combination with exogenously added ATP or adenosine, the pro-inflammatory and anti-inflammatory arms of purinergic signaling. Finally, we analyzed the impact of genetic loss of CD39 on pathophysiologic lung changes associated with lung fibrosis induced by a single-dose whole thorax irradiation (WTI) with 15 Gy. Loss of CD73 in the tumor host did neither significantly affect tumor growth nor the radiation response of the CD39/CD73-negative LLC1 tumors. In contrast, LLC1 tumors exhibited a tendency to grow faster in CD39-/- mice compared to WT mice. Even more important, tumors grown in the CD39-deficient background displayed a significantly reduced tumor growth delay upon irradiation when compared to irradiated tumors grown on WT mice. CD39-deficiency caused only subtle differences in the immune compartment of irradiated LLC1 tumors compared to WT mice. Instead, we could associate the tumor growth and radioresistance-promoting effects of host CD39-deficiency to alterations in the tumor endothelial compartment. Importantly, genetic deficiency of CD39 also augmented the expression level of fibrosis-associated osteopontin (OPN) in irradiated normal lungs and exacerbated radiation-induced lung fibrosis at 25 weeks after irradiation. We conclude that genetic loss of host CD39 alters the tumor microenvironment, particularly the tumor microvasculature, and thereby promotes growth and radioresistance of murine LLC1 tumors. In the normal tissue loss of host CD39 exacerbates radiation-induced adverse late effects. The suggested beneficial roles of host CD39 on the therapeutic ratio of radiotherapy suggest that therapeutic strategies targeting CD39 in combination with radiotherapy have to be considered with caution.